2021
DOI: 10.1016/j.anpede.2021.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of COVID-19 pandemic over acute bronchiolitis hospitalizations in the center and east of Spain

Abstract: Introduction Non-pharmaceutical interventions that have been implemented in southern hemisphere countries because of COVID-19 pandemic declaration in March 2020, have evidenced some unexpected changes in the way of spreading of many other viruses. This study as a part of ECEALHBA’s Project, reports the consequences of COVID-19 pandemic over 2020–2021 bronchiolitis epidemic period in the Central and Eastern regions of Spain. Method Multicenter, observational, descriptive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 34 publications
0
4
1
Order By: Relevance
“…Similarly, this study found that about 50% of the hospitalized children born in 2021 were born in September or October, at the beginning of the RSV epidemic. The length of hospital stay in the present study was nearly 6 days, longer than the 4.4 days reported in Spain and the 2.1 days reported in Australia [ 40 , 45 ]. The extended length of stay in the present study may be due to the younger age of the children hospitalized in Italy.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…Similarly, this study found that about 50% of the hospitalized children born in 2021 were born in September or October, at the beginning of the RSV epidemic. The length of hospital stay in the present study was nearly 6 days, longer than the 4.4 days reported in Spain and the 2.1 days reported in Australia [ 40 , 45 ]. The extended length of stay in the present study may be due to the younger age of the children hospitalized in Italy.…”
Section: Discussioncontrasting
confidence: 69%
“…During the COVID-19 pandemic in the 2020–2021 season, rhinovirus was reported to be primarily responsible for acute respiratory syndrome and hospitalizations for bronchiolitis [ 31 , 33 , 45 ]. This non-enveloped virus is less affected by NPIs, such as handwashing and the use of ethanol-containing disinfectants [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although some authors have speculated on the appearance of a delayed outbreak of AB in Spain during the COVID-19 pandemic 7 , 8 , to our knowledge, this is the first study to describe this particular epidemiological phenomenon, providing results about the seasonal behaviour of different respiratory viruses over several seasons in an area of Spain. It would be of great interest to continue to have similar and broader records in the coming years.…”
Section: Discussionmentioning
confidence: 91%
“…Every year, when winter arrives, respiratory virus infections increase and cases of AB rise to epidemic levels, creating a significant demand for healthcare with a risk of saturating the health system and having a significant socioeconomic impact. However, during the 2020-2021 autumn-winter season, this disease was practically non-existent in Spain and other countries 3 , 5 , 7 , 8 , 9 , 10 , 11 , 12 .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation